Conﬁgurational splitting in Raman scattering spectra of crystals with the order-disorder type phase transitions - Stasyuk, I.V.; Ivankiv, Ya.L. (Condensed Matter Physics, 1999)
A system of equations for the averaged phonon Green function determining the shapes of the lines in Raman scattering spectra is obtained in the coherent potential approximation. Conﬁgurationally split components of the Raman scattering are studied within a simple model. For the KH₂PO₄ and the CsH₂PO₄-type ferroelectrics the possibility to observe the conﬁgurational splitting experimentally is discussed.